Convenient and Scalable Synthesis of Fmoc-Protected Peptide Nucleic Acid Backbone - Feagin, Trevor A.; Shah, Nirmal I.; Heemstra, Jennifer M. (Journal of Nucleic Acids, 2012)
The peptide nucleic acid backbone Fmoc-AEG-OBn has been synthesized via a scalable and cost-effective route. Ethylenediamine is mono-Boc protected, then alkylated with benzyl bromoacetate. The Boc group is removed and replaced with an Fmoc group. The synthesis was performed starting with 50 g of Boc anhydride to give 31 g of product in 32% overall yield. The Fmoc-protected PNA backbone is a key intermediate in the synthesis of nucleobase-modified PNA monomers. Thus, improved access to this molecule is anticipated to facilitate future investigations into the chemical properties and applications of nucleobase-modified PNA.